Negative auditory hallucinations are associated with increased activation of the defensive motivational system in schizophrenia - Anna R. Knippenberg; Sabrina Yavari; Gregory P. Strauss (Schizophrenia Research: Cognition, 2025)
Auditory hallucinations (AH) are the most common symptom of psychosis. The voices people hear make comments that are benign or even encouraging, but most often voices are threatening and derogatory. Negative AH are often highly distressing and contribute to suicide risk and violent behavior. Biological mechanisms underlying the valence of voices (i.e., positive, negative, neutral) are not well delineated. In the current study, we examined whether AH voice valence was associated with increased activation of the Defensive Motivational System, as indexed by central and autonomic system response to unpleasant stimuli. Data were evaluated from two studies that used a common symptom rating instrument, the Psychotic Symptom Rating Scale (PSY-RATS), to measure AH valence. Participants included outpatients diagnosed with SZ. Tasks included: Study 1: Trier Social Stress Task while heart rate was recorded via electrocardiography (N = 27); Study 2: Passive Viewing Task while participants were exposed to pleasant, unpleasant, and neutral images from the International Affective Picture System (IAPS) library while eye movements, pupil dilation, and electroencephalography were recorded (N = 25). Results indicated that negative voice content was significantly associated with: 1) increased heart rate during an acute social stressor, 2) increased pupil dilation to unpleasant images, 3) higher neural reactivity to unpleasant images, and 4) a greater likelihood of having bottom-up attention drawn to unpleasant stimuli. Findings suggest that negative AH are associated with greater Defensive Motivational System activation in terms of central and autonomic nervous system response.